(untitled) (Journal of Global Humanities and Social Sciences, 2024)
As the digital transformation has become an inevitable trend of global economic development, enterprises are facing unprecedented challenges and opportunities. In the context of digital transformation, this paper aims to analyze the financial performance by factor analysis. Article first summarizes the digital transformation of the global economy, industrial structure and the profound influence of enterprise operations, special emphasis on the data in the modern economy and the core position of artificial intelligence for social progress, then, in Vanke group, for example, introduced the digital transformation, including information stage, digital stage and intelligent stage of the concrete implementation and results. By comparing the financial performance changes of Vanke Group before and after the digital transformation of Vanke Group, it is found that the digital transformation has effectively improved the financial performance of Vanke Group.